2013
DOI: 10.1016/j.cmpb.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

ImaGiNe Seldinger: First simulator for Seldinger technique and angiography training

Abstract: Abstract.In vascular interventional radiology, procedures generally start with the Seldinger technique to access the vasculature, using a needle through which a guidewire is inserted, followed by navigation of catheters within the vessels. Visual and tactile skills are learnt in a patient apprenticeship which is expensive and risky for patients. We propose a training alternative through a new virtual simulator supporting the Seldinger technique: ImaGiNe (Imaging Guided interventional Needle) Seldinger. It is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…carotid, femoral and brachial pulse), virtual simulators with haptic interfaces for simulation of pulse palpation in a virtual environment [3,4], hybrid simulators with a physical replica of a pulsating arterial vessel and augmented reality functionalities (i.e. to improve the simulation realism by adding a "virtual jet" of blood in case of a possible needle insertion after pulse palpation) [5,6]. Examples of implementing a pulse simulator include: using an hydraulic interface (with an hydraulic pump to inflate a tube) to provide a physical replica of a pulsating vessel [5,6]; using the acoustic Radiation Pressure (ARP) phenomena generated by focusing multiple ultrasonic transducers to create perceivable vibrations trough an haptic interface [7,8]; integrating different tactile devices, based on a piezoelectric pads, a micro speakers, or a pin array, into a commercial force feedback device (Falcon by Novint Technologies, Inc.) [4].…”
Section: Introductionmentioning
confidence: 99%
“…carotid, femoral and brachial pulse), virtual simulators with haptic interfaces for simulation of pulse palpation in a virtual environment [3,4], hybrid simulators with a physical replica of a pulsating arterial vessel and augmented reality functionalities (i.e. to improve the simulation realism by adding a "virtual jet" of blood in case of a possible needle insertion after pulse palpation) [5,6]. Examples of implementing a pulse simulator include: using an hydraulic interface (with an hydraulic pump to inflate a tube) to provide a physical replica of a pulsating vessel [5,6]; using the acoustic Radiation Pressure (ARP) phenomena generated by focusing multiple ultrasonic transducers to create perceivable vibrations trough an haptic interface [7,8]; integrating different tactile devices, based on a piezoelectric pads, a micro speakers, or a pin array, into a commercial force feedback device (Falcon by Novint Technologies, Inc.) [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many examples of where VR has been used to train the motor skills required to carry out specific medical and surgical procedures (e.g., [6], [10]), including our own work with our collaborators [23], [43] and [30]. Formal validation studies carried out within these projects demonstrated that there is skill transfer from VR to the real world scenario, and that it is possible to discriminate between users with different levels of skill.…”
Section: Training In Vrmentioning
confidence: 99%
“…A number of low and high fidelity simulators exist to aid these part-tasks, which can simulate pulsatile arterial blood flow for vascular access training. More sophisticated simulators allow practise of the Seldinger technique for vascular access 19,20 and numerous simulators are available for training on vascular closure devices.…”
Section: Part-task Training Simulatorsmentioning
confidence: 99%